2017
DOI: 10.1186/s12906-017-1748-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural products isolated from Tetragonula carbonaria cerumen modulate free radical-scavenging and 5-lipoxygenase activities in vitro

Abstract: BackgroundPropolis and cerumen are plant-derived products found in honeybees and stingless bees, respectively. Although propolis is an ancient folk medicine, the bioactivities of cerumen obtained from Australian native stingless bees (Tetragonula carbonaria) have not been widely studied. Therefore, we investigated selected anti-oxidant and anti-inflammatory properties of T. carbonaria cerumen.MethodsA methanolic extract was prepared from the combined cerumen of 40 T. carbonaria hives, and HPLC was used to scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The free radical-scavenging activities of 80 μM DHA, EPA and OA were examined using a colorimetric 1,1-diphenyl-2picrylhydrazyl (DPPH) assay as previously described 54 . Briefly, fatty acids and positive controls (BHT 227 μM; quercetin 50 μM) were incubated with methanolic DPPH solutions (100 μM; 30 min; 22 °C) and absorbance was measured at 518 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The free radical-scavenging activities of 80 μM DHA, EPA and OA were examined using a colorimetric 1,1-diphenyl-2picrylhydrazyl (DPPH) assay as previously described 54 . Briefly, fatty acids and positive controls (BHT 227 μM; quercetin 50 μM) were incubated with methanolic DPPH solutions (100 μM; 30 min; 22 °C) and absorbance was measured at 518 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that oral health indices such as the bleeding index and PI experienced greater improvement in the propolis group. Also, the frequency of teeth retaining their natural colour was significantly higher in the propolis group 22 . Kuo et al in their review study in 2018 reviewed five clinical trials regarding prevention of mucositis in patients undergoing chemotherapy by use of propolis and chlorhexidine mouthwashes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the frequency of teeth retaining their natural colour was significantly higher in the propolis group. 22 Kuo et al…”
Section: Ta B L Ementioning
confidence: 99%
“…[ 54 ] demonstrated that propolis of the Australian species Tetragonula carbonaria inhibits the activity of the enzyme 5-lipoxygenase (5-LOX), which is known to catalyze the production of proinflammatory mediators. In addition, polar extracts of T. carbonaria propolis have been described to have antioxidant properties and to suppress production of the proinflammatory eicosanoid leukotriene B4 in human neutrophils stimulated with ionomycin [ 146 ].…”
Section: Antioxidant and Anti-inflammatory Activities Of Propolis: Chemopreventive Potentialmentioning
confidence: 99%